2021
DOI: 10.1242/dmm.049175
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of brittle cornea syndrome caused by mutation in Zfp469

Abstract: Brittle Cornea Syndrome (BCS) is a rare recessive condition characterised by extreme thinning of the cornea and sclera. BCS results from loss-of-function mutations in the poorly understood genes ZNF469 or PRDM5. In order to determine the function of ZNF469 and to elucidate pathogenic mechanisms, we used genome editing to recapitulate a human ZNF469 BCS mutation in the orthologous mouse gene, Zfp469. Ophthalmic phenotyping showed that homozygous Zfp469 mutation causes significant central and peripheral corneal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…S3A and S3B). The latter point is particularly important for genes such as ZNF469, as its transcript harbors one large coding exon and CRISPR mutations do not lead to nonsense mediated mRNA decay as previously demonstrated for the mouse homolog ( 30 ). Notably, only the targeting of three TFs ( ZNF469 , RUNX1 , TBX3 ) resulted in a significant (FDR < 0.01) downregulation of COL1A1 mRNA (Fig.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…S3A and S3B). The latter point is particularly important for genes such as ZNF469, as its transcript harbors one large coding exon and CRISPR mutations do not lead to nonsense mediated mRNA decay as previously demonstrated for the mouse homolog ( 30 ). Notably, only the targeting of three TFs ( ZNF469 , RUNX1 , TBX3 ) resulted in a significant (FDR < 0.01) downregulation of COL1A1 mRNA (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Both are developmental disorders that feature organ dysfunction from loss of collagen in the eye and musculoskeletal system, respectively. Moreover, deletion of ZNF469 in developing zebrafish decreases synthesis of collagen and proteoglycans ( 39 ); and knockout of Zfp469 in mice recapitulates BCS with decreased collagen deposition in the cornea ( 30 ). No liver phenotypes in the KO mice were described and no adverse effects on viability or fertility were observed ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group demonstrated that induced mutations in a dermal fibroblast ZNF469 gene lead to significant increases in Clusterin, Glypican, and Procollagen C-endopeptidase enhancer 2, and a significant reduction in Thrombospondin while immunofluorescence staining showed a disarray of Collagens I and III, fibronectin, and their receptor integrins [11]. Stanton et al demonstrated in a murine knockout model that an induced loss of function mutation in ZNF469 leads to decreased biomechanical strength of the cornea, likely through ECM dysfunction [12].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the corneal stroma thickness of homozygous mutants is reduced by approximately 50% after conversion according to the thickness ratio of the epithelium and stroma. 18 In this study, we generated a znf469 mutant zebrafish line to elucidate its roles in zebrafish corneal development and applied RNA-sequencing (RNA-seq) to elucidate the possible pathogenesis of BCS induced by znf469 mutations.…”
mentioning
confidence: 99%